Right-hemisphere (spatial?) acalculia and the influence of neglect - Benavides-Varela, Silvia; Pitteri, Marco; Priftis, Konstantinos; Passarini, Laura; Meneghello, Francesca; Semenza, Carlo (Frontiers in Human Neuroscience, 2014)
The present study aimed at exploring basic number and calculation abilities in right-hemisphere damaged patients (RHD), focusing primarily on one-digit orally presented tasks, which do not require explicit visuo-spatial abilities. Twenty-four non mentally-deteriorated RHD patients (12 with clinical neglect (RHDN+), 12 without clinical neglect (RHDN-)), and 12 healthy controls were included in the study. Participants were administered an ad hoc numerical battery assessing abilities such as counting, number magnitude comparison, writing and reading Arabic numerals and mental calculation, among others. Significant differences emerged among healthy controls and both the RHDN+ group and the RHDN- group, suggesting that the mathematical impairment of RHD patients does not necessarily correspond to the presence of left-neglect. A detailed analysis of the sub-tests of the battery evidenced expected differences among RHDN+ patients, RHDN- patients, and controls in writing and reading Arabic numerals. Crucially, differences between RHDN+ patients and controls were also found in tasks such as mental subtraction and mental multiplication. The present findings thus suggest that unilateral right hemisphere lesions may produce specific representational deficits that affect simple mental calculation, and not only the spatial arrangement of multi-digit written numbers as previously thought.